2016
DOI: 10.1016/j.paid.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Rash impulsivity predicts lower anticipated pleasure response and a preference for the supernormal

Abstract: Alcohol, other psychoactive substances, high calorie foods, media entertainment, gaming, and retail products are all forms of modern supernormal stimuli. They exhibit exaggerated features that activate evolved reward systems more so than the natural stimuli for which these systems are adapted. Recent findings suggest that people may vary in the strength of their preference toward supernormal stimuli. The current study assessed whether the two-factor model of impulsivity ) predicts a preference for supernormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Data for this study were collected as part of a large research project, results involving the consumption items and the RD and RI variables have been published previously in separate manuscripts ( Goodwin, Browne, & Rockloff, 2015 ; Goodwin, Browne, Rockloff, & Loxton, 2016 , respectively). Participants consisted of 5,391 (51% female) members of an online survey panel maintained by an agency specializing in the recruitment of survey participants (myopinions.com.au).…”
Section: Methodsmentioning
confidence: 99%
“…Data for this study were collected as part of a large research project, results involving the consumption items and the RD and RI variables have been published previously in separate manuscripts ( Goodwin, Browne, & Rockloff, 2015 ; Goodwin, Browne, Rockloff, & Loxton, 2016 , respectively). Participants consisted of 5,391 (51% female) members of an online survey panel maintained by an agency specializing in the recruitment of survey participants (myopinions.com.au).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that all such supernormal conditions amplify the activity of the underlying neuro-chemical systems beyond their original evolutionary charge (cf. Goodwin et al, 2016;Meshi et al, 2015;Ward, 2013). foundation for Tinbergen's identification of releasers, normal and supernormal, to be open to question.…”
Section: Issue Of Releasersmentioning
confidence: 99%